Review of the metric properties of the Emotional Dysregulation Scale in Mexican adolescents - Marco Antonio Santana Campas; Oscar Ulises Reynoso González; Laura Elena De Luna Velasco; Juan Grapain Contreras (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
Emotional regulation is the process of initiating, maintaining, modulating the intensity and duration of emotional reactions to achieve goals and adapt. Emotional dysregulation has been related to psychopathologies and maladaptive behaviors. Ob-jective: To determine the reliability and factorial structure of the adaptation of the Emotional Dysre-gulation Scale (DERS) to the Mexican population and to propose a rating. An instrumental design was applied with a sample of 858 high school stu-dents between 11 and 17 years of age. The factorial solution obtained showed adequate results: S-B χ² (246): 557.95 (p <.001), CFI: .97, TLI: .96, RMSEA: .04 [CI90% .03-.05], SRMR: .04, as well as acceptable levels of discrepancy between the observed and theoretical covariance matrix, with satisfactory internal consistency, according to McDonald's coefficient, (ω = .932 [CI .925 -.938]). It is concluded that the DERS has adequate psychometric properties for its application and that it is a useful instrument in health and educational institutions for the evaluation and development of strategies for the promotion and prevention of men-tal health difficulties in adolescents.